ASSESSING THE IMPACT OF SUPERVISION AND MANAGEMENT TRAINING ON POLICE OFFICER PERFORMANCE AT NKURENKURU POLICE STATION - Kennedy Kaumba Mabuku (Khazanah Multidisiplin, 2024)
This research explores the impact of supervision and management training on the performance of police officers at Nkurenkuru Police Station, focusing on improving law enforcement effectiveness. Conducted in the Kavango West Region of Namibia, the study aims to understand how training programs influence personnel performance. Qualitative research methods were employed, using semi-structured interviews and thematic analysis for data interpretation. The findings highlight a complex relationship between supervision and management training and police officer performance. While acknowledging some positive impacts of the training, the study identifies various obstacles that hinder its full effectiveness. These challenges include resource limitations, lack of follow-up support, administrative burdens, resistance to change, inadequate integration of training, and heavy workloads. The study suggests the importance of a comprehensive approach to supervision and management training tailored to the needs of law enforcement agencies. Recommendations include customising training programs, increasing participant engagement, and establishing consistent follow-up mechanisms. These insights are not only relevant to Nkurenkuru Police Station but also offer valuable lessons for law enforcement agencies worldwide seeking to optimise their performance through effective training strategies.